Synthesis and Characterization of Dibutyltin(IV) and Triphenyltin(IV) Complexes Derivatives of 3-Methyl-4-nitrobenzoic and 4-Methyl-3-nitrobenzoic Acid and in vitro Cytotoxic Assay on Human Liver Hepatocellular Carcinoma Cells (HepG2) - Win, Yip-Foo; Teoh, Siang-Guan; Ha, Sie-Tiong; Wai, Soon-Han; Yousif, Emad (Asian Journal of Chemistry, 2012)
In this study, two dibutyltin(IV) complexes which are obtained as organodistannoxane dimer with the general formulae of [X-CH3-Y-NO2-C6H3COO(C4H9)2Sn]2O2 (X= meta, Y= para 1; X= para, Y= meta 3) and another two triphenyltin(IV) complexes (monomer) with the general formulae of X-CH3-Y-NO2-C6H3COO(C6H5)3Sn.CH3OH (X= meta, Y= para 2; X= para, Y= meta 4) have been successfully synthesized. The infrared and NMR spectroscopy on the parent acids and their dibutyltin(IV) and triphenyltin(IV) complexes showed that the coordination took place via oxygen atoms from the carboxylate anions. Based on the spectroscopy studies indicated that one methanol molecule also take part in the coordination to tin(IV) atoms moiety in complexes 2 and 4 resulting the tin(IV) atoms moiety are five-coordinated in solid state and four-coordinated in solution state. From the preliminary in vitro cytotoxic assay, complexes 2 and 4 [triphenyltin(IV)] showed better activity compared to complexes 1 and 3 [diorganotin(IV)].